Clinical Manifestations, Risk Factors, and Maternal and Perinatal Outcomes of Coronavirus Disease 2019 in Pregnancy: Living Systematic Review and Meta-analysis. Issue 2 (June 2021) - Allotey, J.; Stallings, E.; Bonet, M.; Yap, M.; Chatterjee, S.; Kew, T.; Debenham, L.; Llavall, A.C.; Dixit, A.; Zhou, D.; Balaji, R.; Lee, S.I.; et al.
Abstract : ( BMJ . 2020;370:m3320) Since its onset, the novel coronavirus disease (COVID-19) caused by the SARS-CoV-2 has caused increased morbidity and mortality worldwide. The pregnant population has been of particular concern, as the effects of COVID-19 on this group and their neonates during and after pregnancy are unknown. Several large case series and systematic reviews of COVID-19 during pregnancy exist, however variance in method, testing and duplicated data have yielded results that at times lack external validity and become quickly outdated. The primary goal of this study was to begin a living (and consistently updated) systematic review to determine clinical manifestations of COVID-19 in pregnant and postpartum women, to identify risk factors for possible complications, and to quantify perinatal and maternal outcomes.